OD OBJAVE DO INTERPRETACIJE: NASR HAMID ABU ZAYD I KNJIŽEVNO PROUČAVANJE KUR’ANA - Kermani, Navid; Fatić, Almir (Novi Muallim, 2022)
UDK 28:1 Prijevod s engleskog: Almir Fatić Ovaj rad se temelji na: Navid Kermani, Offenbraung als Kommunikation. Das Konzept wahy in Nasr Hamid Abu Zayds ‘Mafhum al-nass’ (Frankfurt am Main, 1996). – Rad je preveden iz: Modern muslim intelectuals and the Qur’an, ed. Suha Taji-Farouki, Oxford University Press in association with The Institute of Ismaili Studies, 2004., str. 169-193. (nap. prev.).